2019
DOI: 10.1038/s41598-018-37171-9
|View full text |Cite
|
Sign up to set email alerts
|

Factorial design-assisted supercritical carbon-dioxide extraction of cytotoxic active principles from Carica papaya leaf juice

Abstract: The aims of this study are to investigate the selective cytotoxic activity of supercritical carbon dioxide (scCO2)-extracted freeze-dried leaf juice (FDLJ) of Carica papaya on squamous cell carcinoma (SCC25) cells, and to delineate the best small scale extraction parameters allowing maximal extract activity. Using scCO2 as a solvent, six operating parameters were studied and the supercritical fluid extraction (SFE) process investigated using a factorial design 26-2. The processing values promoting cytotoxic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A total of 11 lipophilic constituents were identified in the CPSCE extract ( Figure 1a). The identified major constituents were α-tocopherol (5), squalene (3), phytol (2), and a mixture of phytosterols such as campesterol (6), stigmasterol (7), and β-sitosterol (8), consistent with those reported in our previous study ( Figure 2) [27]. A number of minor constituents such as hexadecanoic acid (1), γ-tocopherol (4), olean-12ene (9), 13,17-cycloursan-3-one (10), and cycloartenol (11) were also detected in the CPSC extract.…”
Section: Gc-ms Analysis Of Lipophilic Constituents In Cp Leaf Extractssupporting
confidence: 91%
See 2 more Smart Citations
“…A total of 11 lipophilic constituents were identified in the CPSCE extract ( Figure 1a). The identified major constituents were α-tocopherol (5), squalene (3), phytol (2), and a mixture of phytosterols such as campesterol (6), stigmasterol (7), and β-sitosterol (8), consistent with those reported in our previous study ( Figure 2) [27]. A number of minor constituents such as hexadecanoic acid (1), γ-tocopherol (4), olean-12ene (9), 13,17-cycloursan-3-one (10), and cycloartenol (11) were also detected in the CPSC extract.…”
Section: Gc-ms Analysis Of Lipophilic Constituents In Cp Leaf Extractssupporting
confidence: 91%
“…In addition, the extraction yield of CPSCE extracted by scCO 2 + co-solvent was 150% higher than that of CPSC extracted by scCO 2 alone. Interestingly, the scCO 2 extraction yield of papaya leaves was 1.5-3 fold lower than those found in previous study, despite the use of an additional co-solvent [27]. It might be reasoned that in different geographical locations the soil pH promotes the biosynthesis of bioactive compounds.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…At the same time, the critical CO 2 has unusually high compressibility. Near the critical point, slight changes in pressure or temperature cause obvious changes in density of CO 2 , so that the dissolution of CO 2 can be changed simply by adjusting the temperature or pressure of the system to improve the selectivity of extraction ( Khaw et al, 2019 ). Therefore, increasing the solubility of critical CO 2 by increasing the extraction pressure can become the research direction of process optimization.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves were found to be rich in phenolic compounds such as alkaloids, quercetin and kaempferol. On top of that, the leaf extract contains antioxidant compounds such as α-tocopherol, ascorbic acid and flavonoids [19][20][21] . Some case studies reported that the papaya leaves aid for better recovery of dengue in terms of clinical symptoms and platelet counts.…”
Section: Carica Papayamentioning
confidence: 99%